Demographic and Clinical profile of 190 COVID-19 Patients in a Tertiary Care Private Hospital of Dhaka, Bangladesh: An Observational Study (Journal of Medicine, 2020)
From late December’19 till the end of August 2020, in this nine months period, world has lost more than eight hundred thousands people due to COVID-19 pandemic. Clinical data on COVID-19 in Bangladesh is less. The objective of our study was to evaluate demographic and clinical profile with in a defined period among COVID-19 Bangladeshi Patients in a Tertiary Care Private Medical College Hospital of Dhaka. We conducted a retrospective descriptive study on epidemiological & clinical profile along with short term treatment outcomes of 190 COVID-19 patients from COVID dedicated unit of Popular Medical College Hospital (PMCH) during the period of 18th June to 22nd August 2020 (2 months) with a pre-determined case record form (CRF).Among this 190 patients, mean age was found to be 53 years. Highest percentage of patients (44%) belonged to 41-60 years of age. Regarding gender distribution, two-third patients were male (65%) & one-third patients were female (35%). The predominant symptoms of our enrolled patients were fever (88%),cough (81%) , dyspnoea (58%) & fatigue( 50%). Around half of the patients had been suffering from Hypertension (54%) and Diabetes (47%). Almost half of our patients belonged to moderate severity (48%).The duration of Hospital stay was from 1-36 days, mean was 7 days. There was significant difference for severe and non-severe cases (p value 0.01).J MEDICINE JUL 2020; 21 (2) : 82-88